Incentives to promote the development of renewable energy in Poland - Michał Ptak (Economic and Environmental Studies (E&ES), 2014)
The aim of this paper is to analyse the support scheme to promote electricity from renewable sources in Poland. The first part of the paper presents advantages and disadvantages of different instruments which can be used to promote investments in renewable energy projects. These include feed-in tariffs, fixed premiums, green certificates and tender systems. The second part includes an analysis of the instruments used in Poland to support renewable energy. Attention is also paid to the new support scheme included in the draft of the act on Renewable Energy Sources.
Keywords: 330; renewable energy; energy policy; green certificates